Bedside Neonatal Intensive Care Unit Surgery- Myth or Reality! - Shandip Kumar Sinha; Sujoy Neogi (EL-Med-Pub, 2013)
Neonatal transport is associated with complications, more so in sick and unstable neonates who need immediate emergency surgery. To circumvent these problems, surgery in Neonatal intensive care unit (NICU) is proposed for these neonates. This article reviews the literature regarding feasibility of this novel concept and based on the generated evidence, suggest the NICU planners to always include infrastructure for this. Also neonatal surgical team can be developed that could be transported.